2016
DOI: 10.3389/fped.2016.00093
|View full text |Cite
|
Sign up to set email alerts
|

Associations between EBV and CMV Seropositivity, Early Exposures, and Gut Microbiota in a Prospective Birth Cohort: A 10-Year Follow-up

Abstract: Early-life infections with persistent Epstein–Barr virus (EBV) and cytomegalovirus (CMV) are delayed in affluent countries, probably due to alterations in early environmental exposures, such as maternal age, siblings, and day-care attendance. We have previously reported that the timing of EBV and CMV contraction is related both to allergic sensitization and changes in functional competence of immune cells, while the presence/absence of lactobacilli [Lactobacillus (L.) casei, L. paracasei, and L. rhamnosus] or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
(65 reference statements)
1
24
0
2
Order By: Relevance
“…The cohort has been described in detail elsewhere. [9][10][11] Briefly, families living in Stockholm and expecting a child were invited to participate in the study. The invitation was addressed to families where the mother and the father were allergic, where only the mother but not the father had allergy or where none of the parents had allergies.…”
Section: The Prospective Cohortmentioning
confidence: 99%
“…The cohort has been described in detail elsewhere. [9][10][11] Briefly, families living in Stockholm and expecting a child were invited to participate in the study. The invitation was addressed to families where the mother and the father were allergic, where only the mother but not the father had allergy or where none of the parents had allergies.…”
Section: The Prospective Cohortmentioning
confidence: 99%
“…Other studies also demonstrated an association of ethnicity with the prevalence of herpesviridae, although the role of other factors explaining the association such as socio‐economic or lifestyle‐related factors in these studies were less prominent . Another prospective cohort study demonstrated that maternal age was associated with time to infection for EBV and CMV, regardless of other factors such as daycare and siblings . Additionally, they demonstrated that CMV is often acquired earlier than EBV, which might be explained by the immune response after CMV infection.…”
Section: Discussionmentioning
confidence: 97%
“…32,33 Another prospective cohort study demonstrated that maternal age was associated with time to infection for EBV and CMV, regardless of other factors such as daycare and siblings. 34 Additionally, they demonstrated that CMV is often acquired earlier than EBV, which might be explained by the immune response after CMV infection.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…vous system and organs, leading to encephalitis, hepatitis, and Hodgkin lymphoma (2,16). Among herpes viruses, EBV and CMV are more prevalent in the world and are commonly contracted during infancy (17,18). EBV and CMV reside in B lymphocytes and myeloid progenitor cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…EBV has infected more than 90% of individuals around the world and can establish the latency after primary infection (17). Exceptionally, primary infection with EBV in older children can cause acute infectious mononucleosis instead of establishment of latency (18). Moreover, the expression of latency-related proteins and miRNA has been considered to play a role in the pathogenesis of different lymphomas (19).…”
Section: Discussionmentioning
confidence: 99%